Genealogy of Indonesian Islamic Education: Roles in the Modernization of Muslim Society - Azra, Azyumardi (Center for Research and Development of Religious Literature and Heritage, 2015)
Indonesian Islamic education has long and rich history. In fact Islamic education is one of the most important aspects of legacy of Indonesian Islam. Despite changes in the Indonesian history, Islamic education continues to flourish, consisting now at primary and secondary levels of pesantren. Madrasah, and sekolah Islam. While at the tertiary level, Islamic education institutions consist of State Islamic Higher Education (PTAIN/Perguruan Tinggi Agama Islam Negeri) and Private Islamic Higher Education (PTAIS/Perguruan Tinggi Agama Islam Swasta). Both state and prove Indonesian Islam higher education institutions are the largest system in the whole Islamic world. In the last two decades, another significant development in PTAIN is the enlargement of its mandate through the creation of full-fledged Islamic Universities (UIN/Universitas Islam Negeri). With the historic transformation, the roles of Indonesian Islamic higher education is even becoming more and more important.